RESCUING PUBLICNESS FROM ORGANIZATION STUDIES - Jean-Claude Thoenig
Does publicness still make sense as an issue for further research? Classic organizational sociology (or standard theory) has provided a breakthrough for understanding public administration and management, but has not fully explored the agenda. Publicness is analytically characterized by the ownership of two production functions: efficiency (outputs), effectiveness (societal outcomes). While similarities may exist between public and non-public entities on some aspects of their organizational models, the effectiveness function they are accountable for is quite specific. Such a perspective allows public administration and organizational scholars to explore new perspectives such as organizing and organized (or the agenda of extended theory).organizational analysis; publicness; organized; organizing; public administration